Can Agricultural Extension and Input Support Be Discontinued? Evidence from a Randomized Phaseout in Uganda - Ram Fishman; Stephen C. Smith; Vida Bobic; Munshi Sulaiman (Institute of Labor Economics (IZA), 2019)
Many development programs that attempt to disseminate improved technologies are limited in duration, either because of external funding constraints or an assumption of impact sustainability; but there is limited evidence on whether and when terminating such programs is efficient. We provide novel experimental evidence on the impacts of a randomized phase-out of an extension and subsidy program that promotes improved inputs and cultivation practices among smallholder women farmers in Uganda. We find that phase-out does not diminish the use of either practices or inputs, as farmers shift purchases from NGO-sponsored village-based supply networks to market sources. These results indicate short-term interventions can suffice to trigger persistent effects, consistent with models of technology adoption that emphasize learning from experience.
Keywords: O13; O33; I32; Q12; 330; randomized phaseout; subsidies; supply chain; food security; agricultural technology adoption; agricultural extension; high-yielding varieties; randomized controlled trial; Uganda